Update of the list of QPS‐recommended microbiological agents intentionally added to food or feed as notified to EFSA 16: suitability of taxonomic units notified to EFSA until March 2022. (25th July 2022) - ,; Koutsoumanis, Kostas; Allende, Ana; Alvarez‐Ordóñez, Avelino; Bolton, Declan; Bover‐Cid, Sara; Chemaly, Marianne; Davies, Robert; De Cesare, Alessandra; Hilbert, Friederike; Lindqvist, Roland; Nauta, Maarten; et al.
Abstract: The qualified presumption of safety (QPS) approach was developed to provide a regularly updated generic pre‐evaluation of the safety of microorganisms, intended for use in the food or feed chains, to support the work of EFSA's Scientific Panels. The QPS approach is based on an assessment of published data for each agent, with respect to its taxonomic identity, the body of relevant knowledge, safety concerns and occurrence of antimicrobial resistance. Safety concerns identified for a taxonomic unit (TU) are, where possible, confirmed at the species/strain or product level and reflected by 'qualifications'. In the period covered by this statement, no new information was found that would change the status of previously recommended QPS TUs. Of the 50 microorganisms notified to EFSA in October 2021 to March 2022 (inclusive), 41 were not evaluated: 10 filamentous fungi, 1 Enterococcus faecium, 1 Clostridium butyricum, 3 Escherichia coli and 1 Streptomyces spp. because are excluded from QPS evaluation, and 25 TUs that have already a QPS status. Nine notifications, corresponding to seven TUs were evaluated: four of these, Streptococcus salivarius, Companilactobacillus formosensis, Pseudonocardia autotrophica and Papiliotrema terrestris, being evaluated for the first time. The other three, Microbacterium foliorum, Pseudomonas fluorescens and Ensifer adhaerens were re‐assessed. None of these TUs were recommended for QPS status: Ensifer adhaerens, Microbacterium foliorum, Companilactobacillus formosensis and Papiliotrema terrestris due to a limited body of knowledge, Streptococcus salivarius due to its ability to cause bacteraemia and systemic infection that results in a variety of morbidities, Pseudonocardia autotrophica due to lack of body of knowledge and uncertainty on the safety of biologically active compounds which can be produced, and Pseudomonas fluorescens due to possible safety concerns .